Dynamic Tight Glycemic Control During and After Cardiac Surgery Is Effective, Feasible, and Safe - Lecomte, Patrick; Foubert, Luc; Nobels, Frank; Coddens, José; Nollet, Guy; Casselman, Filip; Crombrugge, Paul Van; Vandenbroucke, Geert; Cammu, Guy (Anesthesia and analgesia, 2008)
Tight blood glucose control reduces mortality and morbidity in critically ill patients, but intraoperative glucose control during cardiac surgery is often difficult, and risks hypoglycemia. In this study, we evaluated the safety and efficacy of a nurse-driven insulin protocol (the Aalst Glycemia Insulin Protocol) for achieving a target glucose level of 80-110 mg/dL during cardiac surgery and in the intensive care unit (ICU). We included 483 nondiabetics and 168 diabetics scheduled for cardiac surgery with cardiopulmonary bypass. To anticipate rapid perioperative changes in insulin requirement and/or sensitivity during surgery, we developed a dynamic algorithm presented in tabular form, with rows representing blood glucose ranges and columns representing insulin dosages based on the patients' insulin sensitivity. The algorithm adjusts insulin dosage based on blood glucose level and the projected insulin sensitivity (e.g., reduced sensitivity during cardiopulmonary bypass and normalizing sensitivity after surgery). A total of 18,893 blood glucose measurements were made during and after surgery. During surgery, the mean glucose level in nondiabetic patients was within targeted levels except during (112 +/- 17 mg/dL) and after rewarming (113 +/- 19 mg/dL) on cardiopulmonary bypass. In diabetics, blood glucose was decreased from 121 +/- 40 mg/dL at anesthesia induction to 112 +/- 26 mg/dL at the end of surgery (P < 0.05), with 52.9% of patients achieving the target. In the ICU, the mean glucose level was within targeted range at all time points, except for diabetics upon ICU arrival (113 +/- 24 mg/dL). Of all blood glucose measurements (operating room and ICU), 68.0% were within the target, with 0.12% of measurements in nondiabetics and 0.18% in diabetics below 60 mg/dL. Hypoglycemia < 50 mg/dL was avoided in all but four (0.6%) patients (40 mg/dL was the lowest observed value). The Aalst Glycemia Insulin Protocol is effective for maintaining tight perioperative blood glucose control during cardiac surgery with minimal risk of hypoglycemia.